Integrating Gold-Backed Cryptocurrency for Blockchain Net Settlement to Achieve Future Economic Stability - Mushaddik, Irma Naddiya; Sharofiddin, Ashurov; Hassan, Aznan (Journal of Islam in Asia (E-ISSN 2289-8077), 2023)
The purpose of this research is to study the possibility of Gold-backed cryptocurrency for net settlement through blockchain technology and its implications on economic globally. The paper attempts to explore the challenges in expanding cryptocurrency backed by gold and to develop the new framework on cryptocurrency backed by gold model for net settlement through blockchain technology to achieve economic stability. To achieve the objective of the study qualitative method has been used, such as content analysis and semi-structured interviews. The study is expected that by implementing a gold-backed cryptocurrency will boost intra-country trade. This effect would be more robust than those generated by the existing economic model. An Islamic monetary system in the modern digital era, would modify international monetary relations in the direction of establishing a stable and just global monetary system by merging the Gold-backed cryptocurrency model for blockchain net settlement with an Islamic fiscal policy. The implementation of gold-backed cryptocurrency through blockchain would solve many of economic problems such as inflation, change the value of money, bring stability and sustainability to our financial obligations and transactions.